PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENGATASI SIKAP BELAJAR SISWA DALAM KELAS DI SMA NEGERI 1 GUNUNG TOAR KECAMATAN GUNUNG TOAR - Andika Andika; Sarmidin Sarmidin; Ikrima Mailani (JOM FTK UNIKS (Jurnal Online Mahasiswa FTK UNIKS), 2020)
Observations at SMA Negeri 1 Gunung Toar, Gunung Toar District, symptomswere found in the field, including: Students who often arrive late, play truant, and cheat, dohomework (homework) done when the teacher explains the lesson at school, or does not dowork home (homework) There are still students chatting with my classmates when the teacherexplains the lesson Students dare to hide their friends' bags or stationery, sleep in class,daydream in class, eat in class, and entrust assignments to friends There are some studentscreating a rowdy atmosphere in class when learning takes place and during empty hours so that it disrupts the concentration of other students or other classes who are learning.Thisstudy aims to determine the role of Islamic Religious Education Teachers in OvercomingDisruptive Learning Attitudes of students in classrooms at SMA Negeri 1 Gunung Toar,Gunung Toar District.Based on the results of data collection by observation, interview and documentation,then the data were analyzed descriptively-qualitatively. The Role of Islamic ReligiousEducation Teachers in Overcoming Disruptive Student Learning Attitudes in Classes atSMA Negeri 1 Gunung Toar, Gunung Toar District is by providing verbal and non-verbalactions. that is, with words such as advising, giving guidance and giving warnings and byaction is giving a suspension, credit point, giving a stamped agreement and removingstudents or transferring if the credit point has reached 1000.